Floods in Southeast Asia: A health priority - Jacqueline Torti (Edinburgh University Global Health Society, 2012)
Out of all the natural disasters, floods are the most common in both developed and developing countries, accounting for approximately 40% of all natural disasters. Flooding has severe implications on human health before, during, and after the onset of a flood. Southeast Asia is a region that is especially prone to frequent and severe natural disasters. The Association of Southeast Asian Nations is comprised of Cambodia, Laos, Thailand, Vietnam, Brunei, Malaysia, Indonesia, the Philippines, Singapore and Myanmar. In this manuscript, I discuss why flooding is a problem is Southeast Asia and why I feel flooding warrants attention compared to other problems in the area due to the serious health impactions that arise as a result of flooding. I also explore why flooding warrants attention compared to other health concerns in the region.